SISTEM INFORMASI APLIKASI PADA ALIKA LAUNDRY PADANG - ija nurhayani saogo; wahyuni yahyan; ilham siregar (JENTIK, 2025)
Alika Laundry is a laundry service business operating in Padang City. As the number of customers increases, the manual recording system currently used causes various problems such as difficulties in recording transactions, managing customer data, tracking laundry status, and creating financial reports. This causes operational processes to become less efficient and recording errors often occur. To overcome these problems, a computerized information system is needed that can help manage laundry businesses more effectively and efficiently. This laundry application information system is designed to manage customer data, laundry transactions, laundry status tracking, to report generation. The system is built using the waterfall method with PHP programming language and MySQL database. With this system, it is expected to improve operational efficiency, data accuracy, and service quality to customers.